2017
DOI: 10.1002/jcp.25817
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular transcytosis of albumin in glomerular endothelial cells after endocytosis through caveolae

Abstract: We previously described albumin endocytosis through caveolae in human renal glomerular endothelial cells (HRGECs). This suggested a new albumin transcytosis pathway, in addition to the fenestral pathway. As a next step, we investigated albumin transcytosis in HRGECs after caveolar endocytosis. HRGECs were incubated with Alexa Fluor 488-labeled bovine serum albumin from 0 to 360 min. Next, markers for endosomes, endoplasmic reticulum (ER), golgi apparatus (GA), lysosomes, and proteasomes and Fc receptors, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“… 10 Previous work has indicated that treating cells with endocytosis inhibitors could effectively inhibit various endocytotic pathways, for example, endocytic chlorpromazine (CPZ, interfering with clathrin-dependent endocytosis) 33 , 34 and methyl-β-cyclodextrin (MβCD, disrupting caveola-dependent endocytosis). 35 , 36 We also found that CPZ or methyl-β-cyclodextrin could reduce the cellular uptake of liposomes by L1210 and HeLa cells (Fig. S14 † ).…”
Section: Resultsmentioning
confidence: 72%
“… 10 Previous work has indicated that treating cells with endocytosis inhibitors could effectively inhibit various endocytotic pathways, for example, endocytic chlorpromazine (CPZ, interfering with clathrin-dependent endocytosis) 33 , 34 and methyl-β-cyclodextrin (MβCD, disrupting caveola-dependent endocytosis). 35 , 36 We also found that CPZ or methyl-β-cyclodextrin could reduce the cellular uptake of liposomes by L1210 and HeLa cells (Fig. S14 † ).…”
Section: Resultsmentioning
confidence: 72%
“…Although MNPSNPs are negatively charged [96,97] and hydrophilic [98] due to PEG-coating, pinocytosis (< 500 nm size [99]) could occur, albeit more slowly. In addition, caveolae-mediated endocytosis which exists in muscles, among others [100], could have functioned as transcytosis pathway [101,102]. However, in the clinical scenario of implant infection, increased endothelial permeability is present [103,104] and therewith overcoming the first barrier, the transfer from blood vessel into the infected tissue surrounding the implant, should probably occur.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, intracellular albumin uptake has been demonstrated in hepatocytes and leukocytes as well as in endothelial and epithelial cell lines using fluorescently labeled albumin and confocal microscopy or flow cytometry approaches. 10,22,36,37 Importantly, in these cells, the intracellular albumin signal was shown to colocalize with markers of the endosome-lysosomal compartment. 10,37 In this subcellular compartment, albumin is not a mere bystander but rather is an effector molecule able to block endosomal TLR signaling and the production of cytokines by leukocytes in response to bacterial DNA.…”
Section: Discussionmentioning
confidence: 89%